2022
DOI: 10.1002/aesr.202200132
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric Front Passivation for Cu(In,Ga)Se2 Solar Cells: Status and Prospect

Abstract: Cu(In,Ga)Se2 (CIGSe) solar cells are among the most efficient thin‐film solar cells on lab scale. However, this thin‐film technology has relatively large upscaling losses for commercial technology. To tackle this, paradigm shifts are proposed that allow for simpler, cost‐effective, and efficient CIGSe solar cells. Front passivation using dielectric layers is one of the options being investigated as this is widely used in Si technology. Research on front passivation for CIGSe is in an early stage and no improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 97 publications
(147 reference statements)
0
7
0
Order By: Relevance
“…First, bandgap grading by changing the Ga content in the absorber is considered a traditional way to improve V oc for a thinner absorber layer [15][16][17][18][19][20][21][22][23][24][25][26]. Many research works have delighted the positive impact of bandgap grading profiles in the generation and collection of minority carriers [26][27][28][29][30][31][32][33][34]. It has been found that double grading allows benefiting from the advantages of both high grading at the front and back side of the cell [30,34].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…First, bandgap grading by changing the Ga content in the absorber is considered a traditional way to improve V oc for a thinner absorber layer [15][16][17][18][19][20][21][22][23][24][25][26]. Many research works have delighted the positive impact of bandgap grading profiles in the generation and collection of minority carriers [26][27][28][29][30][31][32][33][34]. It has been found that double grading allows benefiting from the advantages of both high grading at the front and back side of the cell [30,34].…”
Section: Introductionmentioning
confidence: 99%
“…Many research works have delighted the positive impact of bandgap grading profiles in the generation and collection of minority carriers [26][27][28][29][30][31][32][33][34]. It has been found that double grading allows benefiting from the advantages of both high grading at the front and back side of the cell [30,34]. However, Ga grading is not a complete solution for passivation and rear recombination [1,8].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations